2007
DOI: 10.1109/tadvp.2007.898517
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Thermal Moore's Law

Abstract: Thermal design power trends and power densities for present and future single-core microprocessors are investigated. These trends are derived based on Moore's law and scaling theory. Both active and stand-by power are discussed and accounted for in the calculations. A brief discussion of various leakage power components and their impact on the power density trends is provided. Two different lower limits of heat dissipation for irreversible logic computers that have previously appeared in the literature are dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
52
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 128 publications
(52 citation statements)
references
References 48 publications
0
52
0
Order By: Relevance
“…The increasing power densities in various electronic devices including concentrated photovoltaics, power electronics and laser diodes pose significant thermal management challenges for the electronics industry [1][2][3]. Two-phase microchannel heat sinks are attractive to cool advanced electronic devices because they harness the latent heat of vaporization to dissipate high heat fluxes in a compact form factor.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing power densities in various electronic devices including concentrated photovoltaics, power electronics and laser diodes pose significant thermal management challenges for the electronics industry [1][2][3]. Two-phase microchannel heat sinks are attractive to cool advanced electronic devices because they harness the latent heat of vaporization to dissipate high heat fluxes in a compact form factor.…”
Section: Introductionmentioning
confidence: 99%
“…The predicted maximum cooling achieved by the thin-film TEMs, with and without the interfacial resistances included, were 14.9°C and 25°C, respectively [9] for a heat load of 1,300 Wcm −2 . Krishnan et al [11] showed thin-film TEMs to be a viable technology to cool high heat fluxes in electronic equipment. The interfacial Ohmic heating was shown to drastically affect the performance of these TEMs, especially at micron sizes.…”
Section: Introductionmentioning
confidence: 99%
“…T hermal transport limits the performance of many technologies such as micro and nano electronics and optoelectronics, micro-electro-mechanical systems, and important energy technologies including thermoelectric generation, concentrated photovoltaic systems and electrochemical batteries [1][2][3][4][5] . Although significant advances such as microchannels, heat pipes and thermoelectrics 6,7 have been made in thermal devices for various applications in the last few decades, performance is often limited by the interface between these devices and the components whose temperature needs to be controlled 7 .…”
mentioning
confidence: 99%